2021
DOI: 10.3390/foods10102375
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antioxidant and Hypoglycemic Water-Soluble Polysaccharides from Jasmine Tea

Abstract: There have been few studies dealing with chemical elucidation and pharmacological potentials of water-soluble polysaccharides from jasmine tea, limiting their use in functional foods. In this study, water-soluble polysaccharides (named as JSP) were extracted from Jasminum sambac (L.) Aiton tea and fractionated to afford two sub-fractions (JSP-1 and JSP-2). The main structural characteristics of novel JSP sub-fractions were determined by high performance gel permeation chromatography, ultra-performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 37 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…These results indicate the antioxidant and hypoglycemic activities of JSP-1 and JSP. However, JSP-1 had stronger antioxidant and hypoglycemic activities than JSP-2 [ 74 ].…”
Section: Functionmentioning
confidence: 99%
“…These results indicate the antioxidant and hypoglycemic activities of JSP-1 and JSP. However, JSP-1 had stronger antioxidant and hypoglycemic activities than JSP-2 [ 74 ].…”
Section: Functionmentioning
confidence: 99%
“…Jasmine green tea (jasmine tea in short) is a typical scented tea that is reprocessed from processed green tea by absorbing the fragrance of jasmine ( J. sambac ), mainly produced in Fujian Province, Guangxi Province, Sichuan Province in China ( Wu & Yang, 2021 ). The finished jasmine tea has been favoured since antiquity because of its characteristic “lovely fresh” flavour ( Chen et al, 2016 ) and various beneficial health effects, such as antioxidant ( Tang et al, 2021 ), amelioration of depression-like symptoms ( Zhang et al, 2022 ), sedative effects on autonomic nerve and mood states ( Inoue et al, 2003 , Kuroda et al, 2005 ). Jasmine tea that was exported 6,130 tons in 2020 is one of the main agricultural commodities in international trade, widely sold to Japan, Russia, the United States, and other countries ( Ito et al, 2002 , Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The existing studies have shown that jasmine is rich in flavonoids and has anti-inflammatory, analgesic, and antipyretic effects ( 16 ). Moreover, Cheng et al found that jasmine tea contained water-soluble polysaccharides with antioxidant activity and hypoglycemic effects ( 17 ). In addition, jasmine tea also has tranquilizing and anti-anxiety effects ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%